Growth patterns of incipient colonies of Coptotermes havilandi (Isoptera, Rhinotermitidae) initiated in the laboratory from swarming alates - Costa-Leonardo, Ana Maria [UNESP]; Barsotti, Raquel Cristina [UNESP] (My University, 2001)
Fifty two colonies of Coptotermes havilandi were set up under laboratory conditions using alates collected from an urban area during a period of swarming. The first artificial nest used for each royal couple was a 6cm diameter Petri dish (22ml) filled with a moistened matrix of decayed pine sawdust. After 6 months, these colonies were transferred to 250ml plastic containers with the same culturing matrix. After 24 months a census of all colonies was performed. Each young colony had a live royal pair and the population size of all colonies indicated a nonlinear development. The total population (workers + soldiers + immatures + reproductives) of these incipient colonies ranged from 64 to 1, 164, with a mean of 345 individuals. The number of workers ranged from 53 to 830 individuals, and the number of soldiers ranged from 6 to 83. The present data showed a higher population of incipient colonies than our previous record for the species. We also compared the development of 12 transferred colonies to that of 12 untransferred incipient colonies. The results showed a higher population in transferred colonies, but in both incipient colonies (transferred and untransferred) there was a wide variation in total population. The correlation between queen weight and population size was positive in all 24 colonies.